2011
DOI: 10.5402/2011/729040
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Right Ventricular Outflow Tract Tachycardia in a Patient with Isolated Left Ventricular Noncompaction

Abstract: Isolated left ventricular noncompaction is a hereditary cardiomyopathy in which a variety of supraventricular and ventricular arrhythmias could be observed. We report a patient with exercise-induced ventricular tachycardia with left bundle branch block morphology that had characteristics of an idiopathic ventricular tachycardia who was subsequently diagnosed as left ventricular noncompaction. Successful remission of arrhythmia was ensured after the introduction of oral beta-blocker therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Also, we have previously reported two different cases of NC with normal LV function, normal RV MRI findings and presenting with RV outflow tract tachycardia. [6,7] The electrophysiological basis for arrhythmias in patients with NC has not been clearly defined. Even though it may be thought that the presence of NC arrhythmias originating in the RV is coincidental, the possibility of the presence of a cellular abnormality affecting both RV and LV is logical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, we have previously reported two different cases of NC with normal LV function, normal RV MRI findings and presenting with RV outflow tract tachycardia. [6,7] The electrophysiological basis for arrhythmias in patients with NC has not been clearly defined. Even though it may be thought that the presence of NC arrhythmias originating in the RV is coincidental, the possibility of the presence of a cellular abnormality affecting both RV and LV is logical.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic changes or structural abnormalities undetected by imaging modalities may explain these unusual clinical presentations. [5][6][7] Previous case series of idiopathic ventricular arrhythmias originating in the tricuspid anulus have shown that RF ablation is an effective treatment modality. [3,4] However, in patients with myocardial NC, the role of RF ablation has not been well defined and because of uncertainty about the etiology, we chose electrophysiology (EP) study and RF ablation in our patient.…”
Section: Discussionmentioning
confidence: 99%